Masquelet technique with radical debridement and alternative fixation in treatment of infected bone nonunion - Liu, Xuanzhe; Min, Hong Sung; Chai, Yimin; Yu, Xiaowei; Wen, Gen (Frontiers in Surgery, 2022)
Background: Infected bone nonunion (IBN) is the toughest problem in fracture related infection (FRI), leading to high disability and recurrence. The aim of this study was to evaluate the effectiveness of Masquelet technique with radical debridement and alternative fixation in the management of infected bone nonunion. Patients and Methods: A retrospective study of prospectively collected data in 2 trauma centers was performed during the period of 2016-2020. Patients diagnosed as infected bone nonunion were included in this study. The initial implant was removed and all patients received two-stage Masquelet procedure with radical debridement and alternative fixation. The disappearance of inflammatory manifestations and regression of infection indicators (such as IL-6, CRP, WBC) to normal range were regarded as radical debridement. The alternative fixation depended on local soft tissue conditions. Results were evaluated according to clinical and radiographic assessment and patient satisfaction. Results: 23 patients were included in our study. 6 of them received internal fixation, while the other 17 received external fixation. 21 of the 23 cases were successfully reconstructed without infection recurrence, except 2 reinfected cases. Mean full weight bearing time was 6.6 months follow-up post last surgery. 20 out of 23 cases had satisfactory functional outcomes without additional bone or soft tissue comorbidities. Discrepancies in leg length and joint stiffness were observed in 3 cases and marked as unsatisfied results. Conclusions: Infected bone nonunion can be successfully managed using Masquelet technique under radical debridement combined with alternative fixation method.